Defining of MAbs-neutralizing sites on the surface glycoproteins Gn and Gc of a hantavirus using vesicular stomatitis virus pseudotypes and site-directed mutagenesis. (9th January 2019) - Levanov, Lev; Iheozor-Ejiofor, Rommel Paneth; Lundkvist, Åke; Vapalahti, Olli; Plyusnin, Alexander
Abstract : Earlier four monoclonal antibodies (MAbs) against surface glycoproteins Gn and Gc of puumala virus (PUUV, genus Orthohantavirus, family Hantaviridae, order Bunyavirales ) were generated and for three MAbs with neutralizing capacity the localization of binding epitopes was predicted using pepscan and phage-display techniques. In this work, we produced vesicular stomatitis virus (VSV) particles pseudotyped with the Gn and Gc glycoproteins of PUUV and applied site-directed mutagenesis to dissect the structure of neutralizing epitopes. Replacement of cysteine amino acid (aa) residues with alanines resulted in pseudotype particles with diminished (16 to 18 %) neut-titres; double Cys→Ala mutants, as well as mutants with bulky aromatic and charged residues replaced with alanines, have shown even stronger reduction in neut-titres (from 25 % to the escape phenotype). In silico modelling of the neut-epitopes supported the hypothesis that these critical residues are located on the surface of viral glycoprotein molecules and thus can be recognized by the antibodies indeed. A similar pattern was observed in experiments with mutant pseudotypes and sera collected from patients suggesting that these neut-epitopes are utilized in a course of human PUUV infection. These data will help understanding the mechanisms of hantavirus neutralization and assist construction of vaccine candidates.